In vitro and in vivo evaluation of rotary-jet-spun poly(ɛ-caprolactone) with high loading of nano-hydroxyapatite - Andrade, Telmo M.; Mello, Daphne C. R. [UNESP]; Elias, Conceição M. V.; Abdala, Julia M. A.; Silva, Edmundo [UNESP]; Vasconcellos, Luana M. R. [UNESP]; Tim, Carla R.; Marciano, Fernanda R.; Lobo, Anderson O. (Springer Nature, 2019)
Herein, poly(ɛ-caprolactone) (PCL) mats with different amounts of nanohydroxyapatite (nHAp) were produced using rotary-jet spinning (RJS) and evaluated in vitro and in vivo. The mean fiber diameters of the PCL, PCL/nHAp (3%), PCL/nHAp (5%), and PCL/nHAp (20%) scaffolds were 1847 ± 1039, 1817 ± 1044, 1294 ± 4274, and 845 ± 248 nm, respectively. Initially, all the scaffolds showed superhydrophobic behavior (contact angle around of 140 o C), but decreased to 80° after 30 min. All the produced scaffolds were bioactive after soaking in simulated body fluid, especially PCL/nHAp (20%). The crystallinity of the PCL scaffolds decreased progressively from 46 to 21% after incorporation of 20% nHAp. In vitro and in vivo cytotoxicity were investigated, as well as the mats’ ability to reduce bacteria biofilm formation. In vitro cellular differentiation was evaluated by measuring alkaline phosphatase activity and mineralized nodule formation. Overall, we identified the total ideal amount of nHAp to incorporate in PCL mats, which did not show in vitro or in vivo cytotoxicity and promoted lamellar bone formation independently of the amounts of nHAp. The scaffolds with nHAp showed reduced bacterial proliferation. Alizarin red staining was higher in materials associated with nHAp than in those without nHAp. Overall, this study demonstrates that PCL with nHAp prepared by RJS merits further evaluation for orthopedic applications.[Figure not available: see fulltext.]